Science Literacy Profile of Junior High School Students on Global Warming Material (Lembaran Ilmu Kependidikan, 2024)
Understanding science literacy is essential to facilitating effective learning and effectively addressing environmental concerns, as global warming is a complex subject. The purpose of this study is to map the science literacy profile of junior high school students in grade 7 regarding global warming content. Using multiple-choice exams and interviews, a descriptive quantitative method is employed to gather data on science context, science content, scientific competence, and science attitudes. 64 grade 7 students from SMP Negeri 1 Sambong in the Blora district participated in this study. According to the findings, 50% of students' science literacy in the area of global warming fell into the "very poor" category. The science literacy of the students attained an average score of 28% in the context aspect, 14% in the content aspect, 14% in the competency component, and 22% in the science attitude aspect. Based on the average score, it can be inferred that the science literacy skills of the pupils remain in the "very poor" category when considering all four components.  These results have implications for the necessity of creating a science curriculum that emphasizes critical thinking and application in relation to global warming in order to raise students' general science literacy levels.